The Axes of the Controversial Linguistic Foundations according to Sibawayh - Aldalabih, Mohammad Fadl Thlji (Journal of Ecohumanism, 2025)
The primary objective of this research is not to present the controversial aspects between Sibawayh and other scholars, but rather to examine the foundations that Sibawayh used to support his linguistic opinions, which were often opposed by others. The key foundations that Sibawayh relied upon include auditory, analogy, and interpretative axes, as well as deviations from traditional Arab linguistic practices and the languages spoken by the Arabs. Additionally, this research will discuss other relevant foundations throughout. Sibawayh may refer to one of these axes when comparing the opinions of scholars, categorizing some as easy, others as strong, and others with different attributes. The research paper concludes with a series of findings based on this analysis.